2012
DOI: 10.5243/jsswr.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experimental Test of the Elementary School Success Profile Model of Assessment and Prevention

Abstract: The Elementary School Success Profile Model of Assessment and Prevention (ESSP MAP) is an assessment and intervention strategy designed to improve student academic performance and behavior. The current analysis uses a quasi-experimental design to examine the relationship between a 3-year implementation of the ESSP MAP and aggregate academic outcomes. Students in one 3rd grade cohort (2007)(2008)) from 4 schools in 1 district received the intervention as they progressed from 3rd to 5th grade. Longitudinal hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was also reported that university drop-out has increased as a result of not attaining the minimum pass grade, and could be attributable to the students preoccupied with social media sites for the wrong purposes. It was reported by Bowen (2012) that the dropout in Nigeria could cause a national problem when left unabated.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…It was also reported that university drop-out has increased as a result of not attaining the minimum pass grade, and could be attributable to the students preoccupied with social media sites for the wrong purposes. It was reported by Bowen (2012) that the dropout in Nigeria could cause a national problem when left unabated.…”
Section: Objectives Of the Studymentioning
confidence: 99%